PENETAPAN STANDAR WAKTU PROSES DALAM MENINGKATKAN EFEKTIFITAS DAN EFISIENSI PADA PERUSAHAAN KRUPUK LEZAT DESA SUWALAN KECAMATAN JENU KABUPATEN TUBAN - Louse Happy Amira Salatnaya (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
This study examines the standard setting of processing time in increasing effectiveness and efficiency. The standard time is the time needed to complete a certain task at a speed that continues without causing bad results. The purpose of this study is to set a standard production process time to achieve effectiveness and efficiency of production. This research is a study that combines field research and literature. Methods of data collection using observation, interview and documentation techniques, while data analysis techniques using time study analysis. The results showed that the standard time of 860 minutes that had been determined by the company was a deviation of the time study of + 8% so that the realization of the next production process, the company could save on the use of production process time of 66.76 minutes.